Den første norske tesaurus: Ivar Aasens Norsk Maalbunad - Vikør, Lars S. (LexicoNordica, 2011)
This article contains a discussion of the first onomasiological dictionary for Norwegian: Ivar Aasen’s Norsk Maalbunad (published posthumously in 1925). Aasen (1813–1896) was the founder of the dialect-based “Nynorsk” variety of Norwegian, and Norway’s first advanced dialectologist and lexicographer. Norsk Maalbunad was in fact primarily intended by Aasen as an aid in his other lexicographic work, and therefore not published by him (although completed in 1876). Its model was Roget’s Thesaurus, but Aasen’s choice of words and their arrangement were taken from the world of Norwegian farmers, although he also coined abstract words for concepts not covered in everyday popular speech at the time. The article analyses the structure of Norsk Maalbunad and discusses some of the problems Aasen encountered in the development of an adequate modern vocabulary for the new written language.